Utility of Urine Interleukines in Children with Vesicoureteral Reflux and Renal Parenchymal Damage - Nickavar, Azar; Safaeian, Baranak; Valavi , Ehsan; Davoodi , Homa (Urology Journal, 2020)
Purpose: Vesicoureteral reflux (VUR) is the most common risk factor of urinary tract infection in children. Currently, diagnosis of VUR depends on invasive imaging studies, with a high radiologic burden. Therefore, different biomarkers have been introduced for the evaluation of these patients. The objective of this study was to identify alteration of urinary interleukins (ILs) excretion in children with primary VUR and renal parenchymal damage, for further clinical application. Materials and methods: Urinary concentrations of IL-1α, IL-1β, IL-6, and IL-8 were evaluated in 34 children with VUR (cases) and 36 without VUR (control), during 2018-2019. Urinary concentrations of IL-1, IL-1, IL-6 and IL-8 were measured, using polyclonal antibody ELISA kit, and standardized to urine creatinine (Cr). Patients with infectious or inflammatory disorders, urolithiasis, immune deficiency, acute or chronic kidney disease, and secondary VUR were excluded from the study. Results: Mean age of cases (36.00 ± 27.66) had no significant difference with the control (32.86±29.31) group (p=0.44). The majority of patients had moderate VUR (58.8%), followed by severe (35.3%) and mild (5.9%) grades. Urinary concentration of all ILs/Cr were significantly higher in patients with VUR, compared with those without VUR. There was no significant correlation between urine ILs/Cr with age, gender, serum electrolytes, urine specific gravity, renal ultrasound, laterality or severity of VUR, and DMSA renal scan. All urine ILs/Cr had acceptable sensitivity and accuracy for workup of children with primary VUR. Conclusion: Urine IL-1α, IL-1β, IL-6 and IL-8/Cr were sensitive and accurate additionary screening biomarkers in children with primary VUR.